FLUORESCEIN ANGIOGRAPHIC EVALUATION OF PERIPHERAL RETINAL VASCULATURE AFTER PRIMARY INTRAVITREAL RANIBIZUMAB FOR RETINOPATHY OF PREMATURITY. Issue 4 (April 2019) - Harper, C. Armitage; Wright, Lauren M.; Young, Ryan C.; Read, Sarah P.; Chang, Emmanuel Y.
Abstract : Purpose: To evaluate angiographic findings in neonates up to 150 weeks postmenstrual age who received intravitreal ranibizumab for primary treatment of Type 1 retinopathy of prematurity. Methods: Retrospective evaluation of fluorescein angiogram findings was completed for 30 eyes of 16 neonates who received intravitreal ranibizumab as primary treatment for Type 1 retinopathy of prematurity between April 2013 and January 2015. Outcome measures included maturity to Zone III, vascular blunting, vascular loops, vascular dilatation, capillary dropout, and vascular fluorescein leakage. Results: Mean gestational age was 24 1/7 weeks and mean postmenstrual age at time of intravitreal ranibizumab treatment was 35 weeks. Fluorescein angiograms performed at 44 weeks to 150 weeks postmenstrual age showed only 50% of eyes reached vascularization to Zone III; 40% had persistent vascular leakage; and ≥90% exhibited vascular blunting, vascular dilatation, and/or capillary dropout. Conclusion: Although intravitreal ranibizumab is effective in initial cessation of Type 1 retinopathy of prematurity, vascularization to Zone III was only achieved in 50% of eyes in our series and most eyes had fluorescein angiography evidence of vascular anomalies. If future studies are performed comparing treatment with laser photocoagulation to anti–vascular endothelial growth factor, fluorescein angiographic studies should be considered to assess the status of the peripheral retinal vasculature to determine treatment effect. Abstract : Retrospective evaluation of funduscopic and fluorescein angiogram findings was performed in 30 eyes of 16 neonates up to 150 weeks postmenstrual age who received intravitreal ranibizumab as primary treatment for Type 1 retinopathy of prematurity. Late angiographic findings of avascular retina and vascular anomalies indicate an important role for angiographic monitoring in infants receiving intravitreal anti–vascular endothelial growth factor treatment for retinopathy of prematurity.